"One Minute for Your Mind": The Development, Implementation, and Application of Our Mental Health Minute. (July 2020) - Jones, Shawn C. T.; Anderson, Riana Elyse
The dissemination of knowledge concerning psychological problems, practices, and perspectives is often within selective journals requiring a great deal of financial investment or psychological services, which has historically been saddled with cultural incompetence, medical abuse, and subsequent stigma from Black Americans. To combat the confines of information existing only within the ivory tower, two Black psychologists developed a venture to better describe and provide psychoeducation to Black populations via an online edutainment platform. This article describes the development, implementation, and application of the series, titled Our Mental Health Minute, which seeks to reduce stigma, provide relevant information and resources, and increase mental health literacy through educational entertainment. Discussion includes a call to practitioners and researchers to consider creative ways to provide content to populations who are likely to be less able to access mental health materials and services.